Representation of 'Asian' students in French tv programmes - Yeow, E-Lynn (2016)
Over the years, East-Asian populations, especially the Chinese, have become the focus of an exotic, imagined representation of the East, and the Asian student has become a sort of euphemism for Asian communities, at least in the French-speaking context if not elsewhere. This essentialising, reductionist approach contrasts with the concept of ―fluid‖ culture (Bauman, 2004) which insists on the process of identification of individuals who are not mere cultural products as cultures and identities donot existper se (Lavanchy,Gajardo&Dervin, 2011). After addressing the concepts of culture, identity and representations in the media, I analysed in this research how Asian students are portrayed in French TV programmes: are they (still) the archetype of an imagined East or are the media moving away from a stereotyped categorisation of the East for this diasporic population? Using Fairclough‘s (1995) model for critical discourse analysis (CDA), Kerbrat-Orecchioni‘s (1999) Theory of Enunciation and Dervin‘s (2013) Mixed Intersubjectivity, eight videos on Asian students in the French media are analysed. The results show that the discourses on Asian students are edited to only stage cases of academically successful individuals excelling in all fields they participate in. Reportages overwhelmingly portray Asian families as academic elites who become the ‗Asian norm‘. The reportages create an imaginary Asian identity where Confucianism often plays a central role in the characters‘ identifications, even though most of the characters presented no longer live or have never even lived in a so-called Confucian environment. This Othering contributes to representing a community which is out of reach for non-Asian French students, who in contrast to Asian students are less successful and subsequently disempowered because they are not affiliated to the absolutely successful Asian community.